2015
DOI: 10.1519/jsc.0b013e31829cef4e
|View full text |Cite
|
Sign up to set email alerts
|

Palm Cooling and Heating Delays Fatigue During Resistance Exercise In Women

Abstract: We previously reported that cold application to the palms between sets of high-intensity bench press exercise produces an ergogenic effect in men. In this study, we hypothesized that palm cooling (PC) or heating during rest intervals between high-intensity weight training sets will increase total repetitions and exercise volume load (kilograms) in resistance trained female subjects in a thermoneutral (TN) environment. Eight female subjects (mean ± SD, age = 25 ± 6 years, height = 160 ± 6 cm, body mass = 56 ± 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(55 citation statements)
references
References 26 publications
4
48
3
Order By: Relevance
“…The results of this study contrast with previous studies that demonstrated improved performance with cooling between sets during resistance training 7,8 , and decreased RPE 7 . This ergogenic effect is justified by "The Gate Control Theory."…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The results of this study contrast with previous studies that demonstrated improved performance with cooling between sets during resistance training 7,8 , and decreased RPE 7 . This ergogenic effect is justified by "The Gate Control Theory."…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, we can hypothesize that one of the hypotheses for the ergogenic effect in the Kwon 8 study called The Gate Control Theory may not occur in 30 seconds of cooling with BFR. The cooling time was adopted in this study according to the Kaatsu training methodology with time around 20 to 30 seconds 1,32 , being shorter than the studies Kwon 7,8 which was 3 minutes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, using an intermittent palm cooling device during a repeated leg press resistance exercise resulted in a higher power output [145,146]. It has been hypothesized that palm cooling allows a lower level of inhibition in the number of activated motor units, which results in a higher power output and number of repetitions [146].…”
Section: Per-cooling and 'Anaerobic' Performancementioning
confidence: 99%